Radiative heat and mass transfer significance through a permeable vertical plate with rotational effects: An artificial approach using the Levenberg–Marquardt algorithm - R. Kavitha; Kavikumar Jacob; Ahmad Haji Zadeh; Nagarajan Deivanayagampillai (AIP Advances)
We examine a heat-absorbing viscous fluid’s electrically conducting boundary layer flow over a semi-infinite permeable plate in a porous medium inclined at an angle α. Nonlinear partial differential equations are solved using perturbation methods, and graphical analysis is used to determine how parameters impact concentration, temperature, and velocity profiles. Buoyancy forces increase fluid velocity with the increased Grashof number. However, the presence of magnetic (Lorentz) and rotational (Coriolis) effects introduces resistance, leading to a reduction in velocity. A direct relationship is observed between the Grashof number and skin friction, while the radiation parameter inversely affects the Nusselt number. An increased Schmidt number lowers the Sherwood number. We also investigate the impact of rotation on unsteady magnetohydrodynamic slip flow using an Artificial Neural Network (ANN) model employing Levenberg–Marquardt Backpropagation. The ANN accurately predicts flow dynamics and heat transfer using numerical simulation data. Model accuracy is validated through mean squared error graphs, regression analysis, and error histograms, demonstrating reliable fluid dynamics predictions under varying conditions.